Predicting Innovative Work Behavior Through the Perspective of Knowledge Sharing, Perceived Organizational Support, and Psychological Empowerment (Study at The National Narcotics Agency for The Special Region of Yogyakarta) - Rahmawati, Wahyu; Nurmaya, Ema; Sutanto, Aftoni; Hidayat, Abdul Choliq (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the influence of Knowledge Sharing, Perceived Organizational Support, and Psychological Empowerment on Innovative Work Behavior in employees of the National Narcotics Agency for the Special Region of Yogyakarta. The population was all employees of the Provincial National Narcotics Agency as well as employees of the Regency/City National Narcotics Agency in the Special Region of Yogyakarta. The sample measurement technique uses the Slovin formula because the population is known for certain. The sample was 131 employees of the Yogyakarta Special Region National Narcotics Agency, including employees of the Provincial National Narcotics Agency and Regency/City National Narcotics Agency. The sampling technique uses simple random sampling as a data collection method. Hypothesis testing with multiple regression analysis using the Statistical Package for Social Sciences (SPSS). The research results show that Knowledge Sharing has a positive and significant effect on Innovative Work Behavior, Perceived Organizational Support has a positive and significant effect on Innovative Work Behavior, and Psychological Empowerment has a positive and significant effect on Innovative Work Behavior. The three variables simultaneously have a positive and significant effect on Innovative Work Behavior. It is hoped that the results of this relationship research can contribute to theory and practice for organizations in improving Innovative Work Behavior.